LIPID PROFILE OF MALNOURISHED AND NUTRITIONALLY RECOVERED TRAINED AND SEDENTARY RATS (Fiep Bulletin - online, 2014)
The goal of this work was to verify whether malnutrition causes modifications in lipid profile and if nutritional recovery associated or not with exercise (swimming, 30 minutes/day, five days/week during 8 weeks) can interfere in this process. Fifty two Fisher female rats were divided into six groups: Control sedentary (CS), control trained (CT), recovered sedentary (RS), malnourished sedentary (MS) and malnourished trained (MT). It was observed that recovered animals had higher weight gain and food efficiency. There was interaction between exercise and nutritional status for liver weight, with values of group MT being higher than those of MS. Total cholesterol and fractions concentrations were higher in the malnourished animals. Our data show that training reduced cholesterol level only in the animals that received the normoproteic diet, even if they were formerly submitted to malnutrition.
Keywords: Malnutrition; exercise; lipid profile